Création de centres de catégorie 2 placés sous l'égide de l'UNESCO - UNESCO. General Conference, 36th, 2011 (2011, 2011)
Contents: pt.I. Proposal for the establishment in Beijing, China, of an International Research and Training Centre for Science and Technology Strategy. -pt.II. Proposal for the establishment in Lisbon, Portugal, of a Centre for the Advanced Training of Scientists from Portuguese-speaking Countries in Areas of the Basic Sciences. -pt.III. Proposal for the establishment in Almaty, Republic of Kazakhstan, of a Central Asian Regional Glaciological Centre. -pt.IV. Proposal for the establishment in Kaduna, Nigeria, of a Regional Centre for Integrated River Basin Management (RC-IRBM). -pt.V. Proposal for the establishment in Nairobi, Kenya, of a Regional Centre on Groundwater Resources Education, Training and Research for East Africa. -pt.VI. Proposal for the establishment in Nsukka, Nigeria, of an International Centre for Biotechnology. -pt.VII. Proposal for the establishment in Turin, Italy, of an International Research Centre on the Economics of Culture and World Heritage Studies. -pt.VIII. Proposal for the establishment in Amman, Jordan, of an International Museum for Women in the Arts. -pt.IX. Proposal for the establishment in Reykjavik, Iceland, of an International Language Centre. -pt.X. Proposal for the establishment in Marrakech, Morocco, of a Regional Centre for Renewable Energy and Energy Efficiency as a category 2 centre under the auspices of UNESCO; -pt.XI. Proposal for the establishment in Sao Paulo, Brazil, of a Regional Centre of Studies for the Development of the